Contextual Teaching Learning Inovasi dalam Strategi Pembelajaran di Bidang Pendidikan Akuntansi - Christine Dwi; Lidya Agustina (Jurnal Akuntansi)
The aims of educational strategy is to help students see meaning in the academic material they are studying by connecting academic subject with the context of their daily lives. Contextual teaching & learning is one of the learning strategies, that is a new strategy who help help students see meaning in the academic material they are studying by connecting academic subject with the context of their daily lives, and the lecturers being the facilitator. For the future contextual teaching & learning is expected to renewal accounting educational system in Indonesia.